2021
DOI: 10.3389/fpsyg.2021.643758
|View full text |Cite
|
Sign up to set email alerts
|

Trust in the Health System and COVID-19 Treatment

Abstract: COVID-19 continues to spread across the globe at an exponential speed, infecting millions and overwhelming even the most prepared healthcare systems. Concerns are looming that the healthcare systems in low- and middle-income countries (LMICs) are mostly unprepared to combat the virus because of limited resources. The problems in LMICs are exacerbated by the fact that citizens in these countries generally exhibit low trust in the healthcare system because of its low quality, which could trigger a number of unco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
(47 reference statements)
1
20
1
Order By: Relevance
“…In line with previous studies, we have found that the overall trust in scientists (Bicchieri et al, 2021;Sturgis et al, 2021) and the overall trust in the political system (Bruine de Schaeffer, 2021) predict COVID-19-related beliefs. In contrast to studies finding that COVID-19 threat beliefs were related to trust in the health system (Udow-Phillips and Lantz, 2020; Antinyan et al, 2021), we did not find evidence for this relationship. However, we found a reliable relationship between beliefs related to vaccination and beliefs related to COVID-19, suggesting that more specific beliefs about the usefulness of health interventions that are also relevant for COVID-19 are better predictors than the generalized trust in the overall health system.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In line with previous studies, we have found that the overall trust in scientists (Bicchieri et al, 2021;Sturgis et al, 2021) and the overall trust in the political system (Bruine de Schaeffer, 2021) predict COVID-19-related beliefs. In contrast to studies finding that COVID-19 threat beliefs were related to trust in the health system (Udow-Phillips and Lantz, 2020; Antinyan et al, 2021), we did not find evidence for this relationship. However, we found a reliable relationship between beliefs related to vaccination and beliefs related to COVID-19, suggesting that more specific beliefs about the usefulness of health interventions that are also relevant for COVID-19 are better predictors than the generalized trust in the overall health system.…”
Section: Discussioncontrasting
confidence: 99%
“…Rather than modifying their existing beliefs to fit the new facts, people can be prone to motivated reasoning and interpret the new facts differently or disregard them in order to preserve their previous beliefs (Druckman and McGrath, 2019). In particular, people who distrust the health system (Udow-Phillips and Lantz, 2020; Antinyan et al, 2021), scientists (Bicchieri et al, 2021;Sturgis et al, 2021), and the overall political system (Bruine de Schaeffer, 2021) can be more reluctant to believe the official messages about the risk of COVID-19 and less willing to adopt preventative measures such as vaccination. For example, in the United States, changes in political leadership and the related levels of trust in government messaging have been related to changes in beliefs about the risk of COVID-19 and willingness to accept vaccination.…”
Section: Related Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has also shown that confidence in the government [ 54 ], institutional trust [ 55 ], and healthcare system trust [ 56 , 57 , 58 ] were associated with a higher subordination of the recommended behaviors during the COVID-19 pandemic. We also found studies that, like ours, show that trust in medicine (understood as trust in doctors) increases compliance with preventative behavior [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to maintain critical thinking in this case, and often people fail in this task because it is easier to follow emotional thinking (Wynes, 2021;Yu et al, 2021), which has often negatively influenced socio-political decisions, for example, creating and maintaining populist movements, which are stronger in uncertain times (Bone, 2021). Stakeholder accountability moves its actions through a complex situation, especially during an actual socio-economic crisis, where there is a significant impairment in terms of social cohesion and trust between people and institutions (Antinyan et al, 2021;Fikukova et al, 2021;Surina et al, 2021;Ye et al, 2021). The accountability of stakeholders means that a single person or a group of people operate for an individual initiative, without an institutional setting, following their own principles, intrinsic rules, and ethics (Salsbury et al, 2018).…”
Section: Discussionmentioning
confidence: 99%